Beyond Campaigns: A Figurative Language Approach in Nike's Advertisement - Sherish Nazhifah Az Zahra (Passage: Journal of English Language and Literature, 2024)
In marketing, advertising equals sales. One of the essential aspects of expressing a company's identity and product lies in the language used in advertisements. This comprehensive study explores the use of linguistic strategies for persuasion, focusing specifically on incorporating figurative language in advertisements. Synthesizing theoretical foundations, such as Perloff's (2021) view of persuasion, provides valuable insights into the role of linguistic strategies, particularly figurative language, in creating attractive advertising. Through a qualitative analysis of 80 Nike's print, television, and online advertisements, this study sheds light on the 14 strategic types of figurative language they employ. These include analogy, hyperbole, metaphor, irony, and more, intricately categorized based on Peña-Cervel and Ruiz de Mendoza Ibáñez's (2022) framework. Nike's skillful use of figurative language emerges as a key theme that contributes to persuasive communication, highlighted by elements of wit, humor, and cultural resonance. By exploring the presence and absence of certain figurative language types in Nike's advertisements, this study offers insight into how Nike's brand distinguishes itself in the marketing landscape. The findings of this study share implications for marketers, advertisers, and scholars interested in understanding the intricacies of persuasive strategy in advertising campaigns.